IFNβ drives ferroptosis through elevating TRIM22 and promotes the cytotoxicity of RSL3 - Dong, Huiyue; Zhu, Ling; Sun, Jingjing; Chen, Qiuyan; Liu, Pengyang; Zhang, Wei; Zeng, Huajing; Lin, Rong; Yu, Zongyang; Lu, Jun (Frontiers in Immunology, 2025)
BackgroundCyclic GMP-AMP synthase (cGAS)-stimulator-of-interferon genes (STING) pathway is a cytosolic DNA sensor system. The production of this pathway, interferon-β (IFNβ), could suppress the growth of tumor cells, yet it is unclear whether ferroptosis is involved in IFNβ-induced cell death.MethodsThe effects of IFNβ on ferroptosis were analyzed in HT1080, 4T1, HCT116 and 786-O cells. HT1080 and 4T1 cells treated with IFNβ were subjected to RNA-Seq analysis. STAT1, STAT3, TRIM21, and TRIM22 were silenced by siRNAs to examine their effects on IFNβ-induced ferroptosis. The cGAS-STING signaling pathway-activated mice were used to evaluate the effects of IFNβ on ferroptosis in vivo. HT1080 cells, three-dimensional (3D) spheroids, and the xenograft mouse models were treated with IFNβ, RSL3, or IFNβ combination with RSL3 to analyze whether IFNβ enhances RSL3-induced ferroptosis.ResultsHere, we found that IFNβ could promote intracellular Fe2+ and lipid peroxidation levels, and decrease GSH levels in tumor cells. RNA sequencing data revealed that IFNβ induced a transcriptomic disturbance in ferroptosis-related genes. Knockdown of tripartite motif-containing 22 (TRIM22) suppressed the levels of intracellular Fe2+ and lipid ROS. It also reduced heme oxygenase (HMOX1) protein levels and increased ferroptosis suppressor protein 1 (FSP1) levels in HT1080 cells treated with IFNβ. Furthermore, our results illustrated that IFNβ enhanced the RAS-selective lethal 3 (RSL3)-induced ferroptosis and the inhibitory effect of RSL3 on GPX4. Meanwhile, compared to the groups treated with either IFNβ or RSL3 alone, the combination treatment of IFNβ and RSL3 significantly inhibited the growth of HT1080 three-dimensional (3D) spheroids and tumor in a mouse xenograft model.ConclusionsOur work reveals a role for IFNβ in promoting ferroptosis and provides evidence that IFNβ could be used with RSL3 to increase cytotoxic effects in tumor cells.